Improving Brand Image By Maximizing Product Quality, Promotion On Social Media, And E-Wom And Its Implications On Interest In Buying Bening’s Skincare Products - Ramadani, Dinda Fitria; Sarmigi, Elex (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research aims to determine the influence of brand image, product quality, promotion on social media, and E-WOM on product purchase interest both directly and indirectly, where the variables used in this research are product quality, brand image, buyer decision and E-WOM where the buyer’s decision is a variable (Y). This research uses a quantitative approach, which was collected with the help of an online questionnaire using Google Forms. The population of this research is Bening's Skincare in Sungai Penuh City, with a sample of 70 Bening skincare respondents. This research data was analyzed using the Structural Equation Model (SEM) using the SmartPLS.1.2.9 application. This research shows that product quality directly has a positive and significant effect on purchasing decisions. This study shows 0.000 0.05, where e-WOM has a direct positive effect on brand image, product quality on brand image, and product quality on purchasing decisions.